2015
DOI: 10.1186/s40697-015-0043-z
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Native Renal Biopsy Adequacy: A Successful Interdepartmental Quality Improvement Activity

Abstract: BackgroundAn adequate renal biopsy is essential for diagnosis and treatment of medical renal disease.ObjectiveWe evaluated two initiatives to improve adequacy of renal biopsy samples at our centre.DesignRetrospective determination of renal biopsy adequacy.SettingQueen Elizabeth II Health Sciences Centre.PatientsPatients undergoing medical renal biopsies.MeasurementsRenal biopsy adequacy.MethodsThe first initiative was to restrict the performance of biopsies to a smaller group of radiologists and to include a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 16 publications
0
16
0
Order By: Relevance
“…of glomeruli, it is said that for a good interpretation of renal tissue, a sample should have atleast 10 glomeruli. 17 Waldo B et al showed in their study that absence of perinephric bleeding within an hour of post biopsy was predictive of an uncomplicated course while the presence of a perinephric haematoma was not reliably predictive of a clinically significant complication post-renal biopsy. 18 We routinely did post renal biopsy USG to look for any complications but after 24 hrs of biopsy in our cases.…”
Section: And Sharmamentioning
confidence: 96%
“…of glomeruli, it is said that for a good interpretation of renal tissue, a sample should have atleast 10 glomeruli. 17 Waldo B et al showed in their study that absence of perinephric bleeding within an hour of post biopsy was predictive of an uncomplicated course while the presence of a perinephric haematoma was not reliably predictive of a clinically significant complication post-renal biopsy. 18 We routinely did post renal biopsy USG to look for any complications but after 24 hrs of biopsy in our cases.…”
Section: And Sharmamentioning
confidence: 96%
“…For example, antiglomerular basement membrane disease (Goodpasture syndrome) and dense deposit disease are two diagnoses overlooked without IF and EM, respectively. As a result, the classification criteria previously described by Geldenhuys et al (12) theoretically may not directly correlate with whether a pathologic diagnosis can be rendered clinically. Practically, however, of the 10 patients who required a repeat biopsy, none satisfied the utilized numeric criteria of adequacy, a finding that lends credibility to said criteria.…”
Section: Discussionmentioning
confidence: 96%
“…Our study also differs in the pathologic criteria used to assess sample adequacy. Most previous studies base sample adequacy on whether the pathologist was able to render a diagnosis, a subjective standard (12). The numeric criterion utilized in our study is a more stringent and objective criterion, not dependent on an institution's pathology department.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the biopsies contained glomeruli but using the relatively strict Banff criteria about a third of biopsies contained a technically inadequate number of glomeruli [ 10 ]. A quality improvement project aimed at improving transplant biopsy adequacy noted a biopsy inadequacy rate of about 25–30% that was not improved by restricting biopsies to a smaller number of radiologists, labelling biopsy reports with specimen adequacy or immediate examination of cores at the bedside by microscopy [ 13 ]. Another study of transplant biopsy adequacy attained a lower mean number of glomeruli per biopsy (9) with 70% of biopsy containing more than 7 glomeruli and 1 artery [ 9 ].…”
Section: Discussionmentioning
confidence: 99%